Altered Pain Perception in a Young Adult with Childhood Trauma and Suspected Riley-Day Syndrome: A Case Report - Pedro Martínez-Lozano; Maurcio Sousa-Pitti; Natalia Toro-Pérez; Juan Nicolás Cuenca-Zaldívar; Rosana Cid-Verdejo; Oliver Martínez-Pozas; Laura Jiménez-Ortega; Eleuterio A. Sánchez-Romero (Reports)
Background and Clinical Significance: Altered pain perception is a diagnostic challenge for patients with a history of trauma and substance use. Familial dysautonomia (Riley-Day syndrome) may further complicate the sensory profiles. Case Presentation: We describe a male in his late twenties, originally from Central America, with a history of severe childhood trauma and chronic cannabis use, who reported diminished pain perception despite multiple injuries. Despite the absence of nociceptive pain (nociceptive hypoesthesia), abnormal sensations, such as tingling and itching (paresthesia), and occasionally unpleasant burning sensations (dysesthesia) were common symptoms in this case. Diagnosis: Clinical suspicion of familial dysautonomia was raised based on altered pain perception and minor autonomic signs. However, no genetic testing or neurological evaluation was performed. Psychological assessment revealed high levels of neuroticism, depression, and maladaptive coping. The Central Sensitization Inventory (CSI) and the Symptom Severity Scale (SS) further supported the presence of psychological symptoms suggestive of possible central sensitization. Outcome: Functional improvement was observed after a reduction in substance use and implementation of self-directed physical and cognitive rehabilitation. No standardized follow-up or formal interventions were recorded. Conclusions: This case illustrates the complexity of pain modulation in trauma-affected individuals and emphasizes the need for an integrative, interdisciplinary evaluation of atypical pain presentations.